Lignocaine: a new technique for intravenous administration. - Levy, R A (1977)
Current practices of intravenous lignocaine administration may result in a significant drop in blood level between the peak serum level from the initial bolus and the subsequent steady state from the constant infusion. This can cause a significant interval when plasma lignocaine levels are less than therapeutic, and ventricular ectopy may occur. To eliminate this subtherapeutic interval, a new therapeutic approach was devised. Seven patients were studied who had no evidence of congestive heart failure or liver disease. Lignocaine was infused at a rate of 25 mg/min; infusion dosages were selected by patient weight. The above therapeutic regimen eliminated the subtherapeutic hiatus and did not result in clinical toxicity. Therefore, this new infusion technique has significant clinical advantages in patients who require therapy with intravenous lignocaine.